Connecting Participant Observation Positions: Toward a Reflexive Framework for Studying Social Movements. Issue 1 (February 2014) - McCurdy, Patrick; Uldam, Julie
In this article, we argue for the importance of considering participant observation roles in relation to both insider/outsider and overt/covert roles. Through combining key academic debates on participant observation, which have separately considered insider/outsider and overt/covert participant observation, we develop a reflexive framework to assist researchers in (1) locating the type of participant observation research; (2) identifying implications of participant observation for both the research and the subjects under study; and (3) reflecting on how one's role as participant observer shifts over the course of fieldwork and considering the implications of this. To illustrate these dynamics, we draw on two examples from our own ethnographic research experiences in direct action anticapitalist movements.